Option Pricing and the Martingale Restriction - Longstaff, Francis A. (Review of Financial Studies, 1995)
In the absence of frictions, the value of the underlying asset implied by option prices must equal its actual market value. With frictions, however, this requirement need not hold. Using S&P 100 index options data, I find that the implied cost of the index is significantly higher in the options market than in the stock market, and is directly related to measures of transaction costs and liquidity. I show that the Black-Scholes model has strong bid-ask spread, trading volume, and open interest biases. Option pricing models that relax the martingale restriction perform significantly better.